Comparative study of Bi-Te-Se-S mineralizations in Slovak Republic and Transcarpathian region of Ukraine. Part 2. Crystal chemistry and genesis of layered Bi-tellurides - Melnikov, V.; Jeleň, S.; Bondarenko, S.; Balintová, T.; Ozdín, D.; Grinchenko, A. (Мінералогічний журнал, 2010)
Bismuth tellurides of layered structure (tetradymite group) are characteristic minerals of metasomatically altered neovolcanites of Slovakia and Ukrainian Transcarpathians. Tsumoite, pilsenite and joseite (A and B) are established in both regions, but the tetradymite is not found in Transcarpathians. Two new minerals, telluronevskite and vihorlatite, are found in Slovakia. Phase Ві2Те (X-ray, microprobe) that forms epitaxial intergrowths with pilsenite is determined in Transcarpathians (Il'kivtsy). Se-joseite-В, Se-tsumoite, Te-bismuthite, phase ~ Ві2SeS (intermediate phase between nevskite and ingodite) and phase with stoichiometry of А3Х2 (A = Bi; Х = Te, Se, S) are determined in globules of native bismuth (Smerekiv Kamin') by microprobe analysis, but the number of anions Х varies from Bi3Te1.5S0.5 to Bi3TeSe0.5S0.5. The temperature of formation of layered bismuth tellurides is estimated within the interval 350—100 ºС. Телуриди бісмуту шаруватої структури (група тетрадиміту) — характерні мінерали метасоматично змінених неовулканітів Словаччини і Українського Закарпаття. Цумоїт, пильзеніт і жозеіт (А і В) відомі в обох регіонах, але тетрадиміт не знайдений в Закарпатті. У Словаччині відкриті два нових мінерали — телуроневскіт і вигорлатит. У Закарпатті (Ільківці) в епітаксичному зростанні з пільзенітом визначена фаза Ві2Те (рентген, електронний зонд), що утворює епітаксичні зростання з пільзенітом. У глобулах самородного бісмуту (Смереків Камінь) за допомогою електронно-зондового аналізу виявлені Se-жозеїт-В, Se-цумоїт, Те-бісмутиніт, фаза ~Ві2SeS (проміжна між невскітом й інгодитом) і фаза зі стехіометрією А3Х2 (А = Ві; Х = Te, Se, S), але кількість аніонів Х змінюється від Bi3Te1,5S0,5 до Bi3TeSe0,5S0,5. Температурний інтервал утворення шаруватих телуридів бісмуту — 350–100 ºС. Теллуриды висмута слоистой структуры (группа тетрадимита) — характерные минералы метасоматически измененных неовулканитов Словакии и Украинского Закарпатья. Цумоит, пильзенит и жозеит (А и В) установлены в обоих регионах, но тетрадимит в Закарпатье не найден. В Словакии открыты два новых минерала — теллуроневскит и выгорлатит. В Закарпатье (Ильковцы) определена фаза Ві2Те (рентген, электронный зонд), образующая эпитаксические сростки с пильзенитом. В глобулах самородного висмута (Смерекив Каминь) с помощью электронно-зондового анализа определены Se-жозеит-В, Se-цумоит, Те-висмутинит, фаза ~Ві2SeS (промежуточная между невскитом и ингодитом) и фаза со стехиометрией А3Х2 (А = Ві; Х = Te, Se, S), но количество анионов Х изменяется от Bi3Te1,5S0,5 до Bi3TeSe0,5S0,5. Температурный интервал образования слоистых теллуридов висмута — 350–100 ºС.